2020
DOI: 10.1002/emp2.12194
|View full text |Cite
|
Sign up to set email alerts
|

The role of lung ultrasonography in COVID‐19 disease management

Abstract: Coronavirus disease 2019 (COVID‐19) has created unprecedented disruption for global healthcare systems. Offices and emergency departments (EDs) were the first responders to the pandemic, followed by medical wards and intensive care unit (ICUs). Worldwide efforts sprouted to coordinate proper response by increasing surge capacity and optimizing diagnosis and containment. Within the complex scenario of the outbreak, the medical community shared scientific research and implemented best‐guess imaging strategies in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 34 publications
0
24
0
Order By: Relevance
“…More recently [June 2020], Boero et al [31] evaluated the role of LUS in COVID-19 management and concluded that, a growing evidence supports the use of LUS in COVID-19. However, no data of multicenter studies are available.…”
Section: Disucssionmentioning
confidence: 99%
“…More recently [June 2020], Boero et al [31] evaluated the role of LUS in COVID-19 management and concluded that, a growing evidence supports the use of LUS in COVID-19. However, no data of multicenter studies are available.…”
Section: Disucssionmentioning
confidence: 99%
“…Although chest tomography (CT) is the reference standard for diagnosis, LU has been shown to be useful in the pre-hospital setting [ 2 ] and upon hospital admission of COVID-19 patients [ 3 , 4 ]. Respiratory COVID-19 symptoms may persist for at least 60 days in 67% of patients [ 5 ], and while repeat CT may be impractical and/or unsafe for patients and operators, LU may be the default imaging modality for monitoring patients’ condition throughout their hospital stay and, if needed, after discharge [ 6 ]. Agreement with CT seems to be more than adequate in SARS-CoV-2-related pneumonia [ 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…As the disease progresses, the sonographic appearances of pleural line irregularities are more intense, and B lines artifacts and subpleural consolidations increase in frequency and size [ 17 , 18 ]. In our study, we have followed a simplified examination protocol derived from a previous one proposed by Soldati et al [ 19 ]. In our experience, in a significant proportion of patients, it is difficult to obtain a good view of the axillary region and the left antero-inferior sector which is usually occupied by the heart.…”
Section: Discussionmentioning
confidence: 99%